Synthesis and Characterization of New Fluoroquinolones Containing an N Substituted Piperazine Moiety - GHODSI, SHAHRAM; FOULADI, SHAHRBANOO; ALI SAFARI, HAMZE; TAGHI-GANJI, MASOOD (Asian Journal of Chemistry, 2010)
N-(Aryl)piperazinyl quinolone derivatives having a hydroxyimino/ keto-substituent have been synthesized. Here, intermediate compounds (1-3) were synthesized in the presence of bromine in acetic acid. Then these compounds were reacted with ciprofloxacin in the presence of NaHCO3 to give ciprofloxacin derivatives (4-7). All the products were confirmed by IR, Mass, 1H NMR or 13C NMR spectra and elemental analysis.